1999
DOI: 10.1016/s1097-2765(00)80345-7
|View full text |Cite
|
Sign up to set email alerts
|

A Xenopus Protein Related to hnRNP I Has a Role in Cytoplasmic RNA Localization

Abstract: Cytoplasmic localization of mRNA molecules is a powerful mechanism for generating cell polarity. In vertebrates, one paradigm is localization of Vg1 RNA within the Xenopus oocyte, a process directed by recognition of a localization element within the Vg1 3' UTR. We show that specific base changes within the localization element abolish both localization in vivo and binding in vitro by a single protein, VgRBP60. VgRBP60 is homologous to a human hnRNP protein, hnRNP I, and combined immunolocalization and in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
232
1
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(242 citation statements)
references
References 44 publications
5
232
1
4
Order By: Relevance
“…More recently, PTB was also found associated with the 3'UTR of the ATP synthase b-subunit, where it helps enhancing translation in a cap-independent manner [62]. In addition to its role in splicing and translation regulation, PTB is implicated in 3'-end processing [63,64], localization [65,66], and stability [67 -75] of various cellular mRNAs. In these systems, PTB acts through pyrimidine-tract binding sites within 5' and/or 3'UTRs.…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, PTB was also found associated with the 3'UTR of the ATP synthase b-subunit, where it helps enhancing translation in a cap-independent manner [62]. In addition to its role in splicing and translation regulation, PTB is implicated in 3'-end processing [63,64], localization [65,66], and stability [67 -75] of various cellular mRNAs. In these systems, PTB acts through pyrimidine-tract binding sites within 5' and/or 3'UTRs.…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
“…Vol. 65,2008 Review Article 521 to function through an interaction with PTB, and might facilitate the identification of novel PTB targets. For example, many studies identified PTB binding sites by boundary analyses, gel shift experiments and cross-linking [10,15,22,32].…”
Section: How Can the Ptb Structures Explain Its Multiple Functionsmentioning
confidence: 99%
“…It is now widely believed that PTB functions as a negative regulator of pre-mRNA splicing, blocking the inclusion of numerous alternative exons into mRNA (Black, 2003), including its own exon . Besides roles in splicing, PTB has also been implicated in the regulation of other aspects of RNA metabolism, such as premRNA polyadenylation (Castelo-Branco et al, 2004), mRNA stability (Kosinski et al, 2003;Knoch et al, 2004), mRNA export from the nucleus (Zang et al, 2001) and mRNA localization in the cytoplasm (Cote et al, 1999). In addition, PTB is involved in the control of cap-independent translation driven by the internal ribosomal entry site (IRES).…”
Section: Introductionmentioning
confidence: 99%
“…RRM 1 and 2, in the N-terminal half of PTB, are required for PTB oligomerization and other protein-protein interactions, whereas RRM 3 and 4, in the C-terminal half of PTB, are necessary for the RNA-binding activity [11]. PTB is involved in multiple steps of pre-mRNA processing, including tissue-specific splicing [12], mRNA localization [13,14], regulation of polyadenylation [15], and transport of hepatitis B viral unspliced mRNA from nucleus to cytoplasm [16]. PTB localizes mainly in the nucleus and can shuttle between the nucleus and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%